Charité bien ordonnée. Acteurs et institutions de la tsédaqah en Europe méditerranéenne au bas Moyen Âge - Claude Denjean; Juliette Sibon; Claire Soussen (Les Cahiers de Framespa)
What were the stakes of the implementation of the tsedaqah in Mediterranean Europe during the Late Middle Ages? Although the sources are incomplete and scattered because of the loss and of the dispersal of the medieval Jewish communities’ archives, the comparison with the Christian majority’s charities reveals a Jewish specificity: the medieval Jews developed more varied kinds of charity than the Christians and the nature of their actions was more «social» than «religious». The study of the tsedaqah’s Latin and Hebraic medieval sources also enables historians to write a history of the Jewish elites. Finally, if the Tsedaqah is a «halakhic» obligation, its respect in the medieval society was submitted to the goodwill of powerful individuals and it thus met various resistance according to the communities and the periods.